Whole-transcriptome analysis reveals the profiles and roles of coding and non-coding RNAs during hair follicle cycling in Rex rabbits - Jie Wu; Jiamin Zhai; Haofan Jia; Ifeanyi Solomon Ahamba; Xianggui Dong; Zhanjun Ren (BMC Genomics)
Abstract Background Rex rabbit is famous for its silky and soft fur coat, a characteristic predominantly attributed to its hair follicles. Numerous studies have confirmed the crucial roles of mRNAs and non-coding RNAs (ncRNAs) in regulating key cellular processes such as cell proliferation, differentiation, apoptosis and immunity. However, their involvement in the regulation of the hair cycle in Rex rabbits remains unknown. Results In this study, we identified the hair follicle stages of Rex rabbits aged 3 to 5.5 months. Skin samples collected at 4, 5 and 5.5 months, representing the morphological features of the anagen, catagen and telogen stage separately, were finally selected for whole-transcriptome analysis. 25,736 mRNA, 8280 lncRNA, 24,885 circRNA and 1138 miRNA transcripts were identified. 6027 differently expressed mRNAs (DEGs), 2381 differently expressed lncRNAs (DELs), 438 differently expressed circRNAs (DECs) and 167 differently expressed miRNAs (DEMs) were detected in the anagen vs. catagen (AvC) comparison. 4092 DEGs, 1540 DELs, 356 DECs and 141 DEMs were detected in the anagen vs. telogen (AvT) comparison. 2290 DEGs, 779 DELs, 249 DECs and 92 DEMs were detected in the catagen vs. telogen (CvT) comparison. DEGs were primarily enriched in GO items including plasma membrane, integral component of plasma membrane and extracellular space. KEGG enrichment analysis revealed that DEGs were mainly enriched in PI3K-Akt signaling pathway, cell cycle and Wnt signaling pathway (p < 0.05). KEGG analysis showed trans-acting genes of DELs were significantly enriched in Hippo signaling pathway, PI3K-Akt signaling pathway and Melanogenesis. Target genes of DEMs were mainly enriched in MAPK signaling pathway, Wnt signaling pathway, ECM-receptor interaction and Signaling pathways regulating pluripotency of stem cells. Based on the ceRNA mechanism, lncRNA/circRNA-miRNA-mRNA networks were constructed involving 9 DECs, 437 DELs, 50 DEMs and 416 DEGs. Conclusions Totally, this study provides comprehensive insights into the expression patterns of protein-coding genes and non-coding transcripts throughout the HF cycle, and enhancing the understanding of the regulatory mechanisms underlying mammalian hair fiber development.